The Influence of Mangarock Online Comics in Teaching Writing a Narrative Text - Muhamad Sofian Hadi; Lidiyatul Izzah; Ineke Larasati (Universitas Pendidikan Mandalika, 2021)
Manggarock online comics are used by many researchers in enhancing students’ language skills. This study aims to investigate the effectiveness of Manngarock online comics to improve students' writing skills at the ninth-grade students of SMP Harapan Masa, Depok, Indonesia. This study is categorized as a quantitative study using Pre-experimental design. To attain the data, researchers employ writing tests. The sample of this study is all students of the ninth-grade students of SMP Harapan Masa. The students are subjected to Manggarock online comics. To know the efficacy of Manggarock online comics, researchers apply statistical analysis, which is t-test. The students’ writing skills in the pre-tests and the post-test are calculated using descriptive statistical analysis. Based on the results of analysis, the mean score of students is 79.26. meanwhile, the value of t-test (16.243) was higher than t-table (2.015) in a significant level of 5% (0.05). Therefore, the alternative hypothesis (Ha) proposed was accepted while the null hypothesis was rejected. From the results of this analysis, this study can be concluded that the Manggarock online comics have a positive effect on students' writing skills at the ninth-grade students.